The Study of Gesture in Mind Your Language Movie Based on George Yule Perspective - Maftuhatul Faizah; Mutmainnah Mustofa; Abd Ghafur; Nurhasanah Nurhasanah; Iqbal Rafiqi (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2021)
This research examined the use of gesture on Mind Your Language movie season 1-5 perspective George Yule perspective. Mind Your Language movie is about condition of school or class that students from different country such as Italy, Germany, Greece, Spain, France, China, Japan, India and Pakistan. The objectives are to know the gesture used and how the gesture used on Mind Your Language movie based on George Yule perspective. The researcher used documentation to collect the data. During the process of research process, researchers here should see and hear repeatedly from “The Mind Your Language Movie”, then researchers showing the picture which one is showing the gesture, make every effort to collect and copy data which is related to the research. After that, the researchers finally processed it by using content analysis in a gesture based on George Yule perspective that are three Iconic, Deictic, and Beats. The result of this study is the researcher finds thirty eight gestures based on George Yule perspective that are iconic are twenty, deictic seven, and beats eleven. Each of the three gestures has different language functions ad meaning. Gestures on this movie used by teacher and students both in the classroom or outside the classroom.